Activation of AMPA receptor in the infralimbic cortex facilitates extinction and attenuates the heroin-seeking behavior in rats. (26th January 2016) - Chen, Weisheng; Wang, Yiqi; Sun, Anna; Zhou, Linyi; Xu, Wenjin; Zhu, Huaqiang; Zhuang, Dingding; Lai, Miaojun; Zhang, Fuqiang; Zhou, Wenhua; Liu, Huifen
Highlights: Activation of infralimbic cortex by an AMPA receptor potentiator facilitates extinction. Activation of infralimbic cortex decreases the heroin-seeking induced by cues. Expression of GluR1 in infralimbic cortex and NAc increases after activation of AMPA receptors. Abstract: Infralimbic cortex (IL) is proposed to suppress cocaine seeking after extinction, but whether the IL regulates the extinction and reinstatement of heroin-seeking behavior is unknown. To address this issue, the male SD rats were trained to self-administer heroin under a FR1 schedule for consecutive 14 days, then the rats underwent 7 daily 2 h extinction session in the operant chamber. The activation of IL by microinjection PEPA, an allosteric AMPA receptor potentiator into IL before each of extinction session facilitated the extinction responding after heroin self-administration, but did not alter the locomotor activity in an open field testing environment. Other rats were first trained under a FR1 schedule for heroin self-administration for 14 days, followed by 14 days of extinction training, and reinstatement of heroin-seeking induced by cues was measured for 2 h. Intra-IL microinjecting of PEPA at 15 min prior to test inhibited the reinstatement of heroin-seeking induced by cues. Moreover, the expression of GluR1 in the IL and NAc remarkably increased after treatment with PEPA during the reinstatement. These finding suggested that activation of glutamatergic projection from IL to NAc shell may be involved in the extinction and reinstatement of heroin-seeking.